Acute myocardial infarction and stroke registries. The Italian experience (Epidemiology, Biostatistics, and Public Health, 2022)
Cardiovascular diseases (CVD) are the leading causes of death and hospitalisation in nearly all European countries and accounted for almost 40% of all deaths in 2013. With the exception of few rigorous but limited studies carried out in some geographical areas, data available on CVD incidence and prevalence is generally limited and of poor quality, despite the magnitude of the CVD phenomenon. The EUROCISS Project, supported by the Health Monitoring Programme of the DG SANCO from 2000 to 2007, provided general guidance and updated methods for the surveillance of Acute Myocardial Infarction and Stroke. The Italian population-based registry of major coronary and cerebrovascular events was set up following EUROCISS recommendations; it also took into account the experience acquired by Italy in the MONICA project since the mid-1980s and continued with the coordination of the EUROCISS The project: “A population-based AMI register: assessing the feasibility for a pilot study to implement a surveillance system of acute myocardial infarction (AMI) in Mediterranean countries according to EUROCISS recommendations” in the framework of the EuroMed Programme, followed major practical and operative issues for the implementation of a population-based registry for coronary and cerebrovascular events, which are here described. This paper includes the definition of target population, data sources, events, indicators, quality methods, and the description of a software used to implement the registry.